Analysis of the prevalence and incidence of pseudohypoparathyroidism in Poland based on National Health Fund data with clinical presentation of own cases - Zygmunt, Arkadiusz; Pacocha, Monika; Domanska-Czajka, Agnieszka; Skowronska-Jozwiak, Elzbieta; Lupinska, Anna; Stawerska, Renata; Wojciechowska-Durczynska, Katarzyna; Gach, Agnieszka; Karbownik-Lewinska, Malgorzata; Lewinski, Andrzej (Frontiers in Endocrinology, 2025)
IntroductionPseudohypoparathyroidism (PHP) is a rare genetically determined disease with a wide range of symptoms related to target organs’ resistance to parathyroid hormone (PTH). Lack or insufficient action of PTH on effector organs causes hypocalcemia and hyperphosphatemia. Some patients may have characteristic features of Albright hereditary osteodystrophy (AHO).MethodsWe estimated the prevalence and incidence of PHP using National Health Fund (NHF) data between 2013 and 2023.ResultsThe prevalence was 0.62-0.64/100,000 person-years for Poland and 1.11-1.47/100,000 person-years for the Lodz Voivodeship, depending on the analysis period, i.e., between 2013 and 2019, 2020 and 2021, and 2022 and Oct 2023. During these periods in Poland, PHP was diagnosed for the first time in 282, 32, and 29 patients, respectively, which means that the incidence was 0.19/1,000,000, 0.48/1,000,000, and 0.46/1,000,000 person-years, respectively. In all periods, there were more females in the adult group than in the pediatric group. The study also analyzed data on 19 patients with PHP who have been followed at the Polish Mother’s Memorial Hospital – Research Institute (PMMH-RI), describing the clinical presentation of the disease, treatment, and difficulties in establishing the proper diagnosis.DiscussionIn order to quickly establish the correct diagnosis, it is crucial to collect detailed medical interviews with a family history of the disease. It is also essential to carefully perform a physical examination, looking for non-specific symptoms. It’s also important to check a broader panel of biochemical tests at the beginning of the diagnosis, characterizing calcium-phosphate homeostasis rather than just the concentration of total calcium in serum.